MANAJEMEN PENGELOLAAN DAN PELAYANAN BARANGDI GUDANG YANG DILAKSANAKAN OLEH PT. FAUHAN LOGISTICS DI PELABUHAN - Muhammad Syukri (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
Warehousing is a process of logistical activities / goods in warehouses, both administrative and operational that are related to administration, work procedures and spatial planning, starting from receiving, recording, importing, storing, storing, regulating, accounting, maintaining, spending and distribution activities that end on the warehouse manager's accountability report. The series of activities is to support a work unit system in order to achieve the overall effectiveness goals of the organization's efficiency body. This study is to see how the role of warehouses in the service of goods in port by PT. Fauhan Logistics Palembang and How is the mechanism of quality and quantity when the goods / cargo are in the warehouse by PT. Fauhan Logistics Palembang, This research is a qualitative descriptive study that is an evaluation research that aims to assess the extent to which the variables studied are in accordance with the specified benchmarks. In the service of goods provided by PT. Fauhan Logistics Palembang is transporting rubber from factories to then be stored and shipped to the destination country. In service, the warehouse plays a very important role during the preparation of goods, namely as a distribution center for goods to be sent, requires a place to store before it can be sent. The quality and quantity mechanism when the goods / cargo is in the warehouse starts from Before carrying out the accumulation of goods / cargo in the warehouse, the shipper must show the documents required by the warehouse. Warehouse documents that must be prepared include but not limited to incoming Delivery Order and Shipping instructions, which explain everything about the item in full, ranging from type of goods, quantity of goods, size of goods, shipper, loading and unloading company, name of ship, port of destination , then the goods will be piled into the warehouse and will wait for the process to be shipped according to the specified schedule. Handling of goods activities in the port stacking warehouse, namely receiving goods, storing goods in accordance with its requirements, maintaining goods, maintaining cleanliness of the space where the goods are stored and removing goods according to the needs.